Pollution tolerance performance index for plant species using geospatial technology: evidence from Kolaghat Thermal Plant area, West Bengal, India - Maity, Shibdas; Mondal, Ismail; Das, Biswanath; Mondal, Amal Kumar; Bandyopadhyay, Jatisankar (Spatial information research (Online), 2017)
Pollution is a global phenomenon which has completely transformed the socio-economic scenario in urban areas all over the world we also care about it. Although the plant has a number of benefits, the lack of treatment of the fly ash generated from this plant has been detrimental to the productivity and quality of the main commercial crops of the surrounding area and is also responsible for some changes in the land use pattern. Studies were made to assess the impact of a thermal power plant located at Kolaghat on vegetation and water in surrounding areas. Pollutant concentration in the area gradually increased along a belt in the prevailing wind direction and a gradient of structural and functional changes in aquatic plants was observed. Natural vegetation in the area varied significantly at different sites and on the basis of plant responses can be classified as insensitive, intermediate and sensitive repetitively. The effect of the power plant emissions on water, soil and eco-physiological characteristics such as chlorophyll content, relative water content, ascorbic acid, it’s seemed to be a function of the pollutant gradient existing in the area. There was a relationship between plant responses and changes in the chemical factors of water, soil and plants due to pollution of Thermal Power Plant. According to pollution tolerance performance index such types of plants species play an importance role for green development in Kolaghat Thermal Power area.